Different Waterlogging Depths Affect Spatial Distribution of Fine Root Growth for Pinus thunbergii Seedlings - Fujita, Saki; Noguchi, Kyotaro; Tange, Takeshi (Frontiers in Plant Science, 2021)
The increase of waterlogged environments at forests and urban greenery is of recent concern with the progress of climate change. Under waterlogging, plant roots are exposed to hypoxic conditions, which strongly affects root growth and function. However, its impact is dependent on various factors, such as waterlogging depth. Therefore, our objective is to elucidate effects of different waterlogging depths on Pinus thunbergii, which is widely used for afforestation, especially at coastal forests. We conducted an experiment to examine growth and morphology of fine roots and transpiration rates using two-year-old seedlings under three treatments, 1) control (no waterlogging), 2) partial waterlogging (partial-WL, waterlogging depth= 15 cm from the bottom), 3) full waterlogging (full-WL, waterlogging depth= from the bottom to the soil surface, 26 cm). As a result, fine root growth and transpiration were both significantly decreased at full-WL. This was likely due to the damage of pre-existing roots. However, for partial-WL, fine root growth was significantly increase compared to control and full-WL at the top soil, where it was not waterlogged. Additionally, transpiration which had decreased after 4 weeks of waterlogging, showed no significant difference compared to control after 8 weeks of waterlogging. This recovery is to be attributed to the increase in fine root growth at non-waterlogged top soil, which compensated for the damaged roots at the waterlogged bottom soil. In conclusion, this study suggests that P. thunbergii is sensitive to waterlogging, however, can adapt to waterlogging by plastically changing the distribution of fine root growth.